In situ controlled rapid growth of novel high activity TiB2/(TiB2–TiN) hierarchical/heterostructured nanocomposites - Wang, Jilin; Liao, Hejie; Ji, Yuchun; Long, Fei; Gu, Yunle; Zou, Zhengguang; Wang, Weimin; Fu, Zhengyi (Beilstein Journal of Nanotechnology, 2017)
In this work, a reaction coupling self-propagating high-temperature synthesis (RC-SHS) method was developed for the in situ controlled synthesis of novel, high activity TiB2/(TiB2–TiN) hierarchical/heterostructured nanocomposites using TiO2, Mg, B2O3, KBH4 and NH4NO3 as raw materials. The as-synthesized samples were characterized using X-ray diffraction (XRD), scanning electron microscope (SEM), X-ray energy dispersive spectroscopy (EDX), transition electron microscopy (TEM), high-resolution TEM (HRTEM) and selected-area electron diffraction (SAED). The obtained TiB2/TiN hierarchical/heterostructured nanocomposites demonstrated an average particle size of 100–500 nm, and every particle surface was covered by many multibranched, tapered nanorods with diameters in the range of 10–40 nm and lengths of 50–200 nm. In addition, the tapered nanorod presents a rough surface with abundant exposed atoms. The internal and external components of the nanorods were TiB2 and TiN, respectively. Additionally, a thermogravimetric and differential scanning calorimetry analyzer (TG-DSC) comparison analysis indicated that the as-synthesized samples presented better chemical activity than that of commercial TiB2 powders. Finally, the possible chemical reactions as well as the proposed growth mechanism of the TiB2/(TiB2–TiN) hierarchical/heterostructured nanocomposites were further discussed.
Keywords: chemical activity; hierarchical/heterostructures; self-propagating high-temperature synthesis; TiB2; TiN